If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = c + 5 + -16 Reorder the terms: 3 = 5 + -16 + c Combine like terms: 5 + -16 = -11 3 = -11 + c Solving 3 = -11 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 3 + -1c = -11 + c + -1c Combine like terms: c + -1c = 0 3 + -1c = -11 + 0 3 + -1c = -11 Add '-3' to each side of the equation. 3 + -3 + -1c = -11 + -3 Combine like terms: 3 + -3 = 0 0 + -1c = -11 + -3 -1c = -11 + -3 Combine like terms: -11 + -3 = -14 -1c = -14 Divide each side by '-1'. c = 14 Simplifying c = 14
| 10y=4y+10+5y | | 0.428h=9 | | 2-6x=52 | | 9x-(3x+4)=15+5(2-x) | | x-0.7=9.09 | | 2x-3=s | | 4x-7-2=x+18 | | t^2=8-2t | | 11+4a-2a=73-10 | | w^2=-30-11w | | w^2-12w+36=0 | | 7=y-4 | | 36v^2-25g^2=0 | | -8x^6-16x^5+384x^4=0 | | b^2-b-12=0 | | 2x-x-10=0 | | 2(2x)+2x= | | (x+6y-4z)-(x-5y+3z)= | | 100=.42x | | x+(x+832)=2976 | | 25s^2-40s+16=0 | | 3y^2+10y=7 | | 24y^2-10yz-25z^2=0 | | 3(W+2)-4(W+3)=0 | | 24y^2-10yz-25z^2=O | | 0.125(-9.6-3.8)= | | 12E-4=0 | | 3y^2+10y-7=0 | | 30y^2-19y-4=0 | | 8x-7y=-10 | | -5+12= | | -2x+5=29 |